Kesiapan Sumber Daya Manusia Kabupaten Tolitoli Menghadapi Transformasi Digital dan Otomasi - Jaya Pernama, Ilham; Syahputra, Rendy Aziz; Morad, Ayu Wandira M.; Widodo, Julistyono (Tolis Ilmiah : Jurnal Penelitian, 2025)
Digital transformation and automation have posed major challenges for many regions, including Tolitoli Regency in Central Sulawesi. Amidst the dominance of traditional economic sectors and limited access to technology, the readiness of human resources (HR) is essential in adapting to the changing times. This study aims to assess the readiness level of Tolitoli’s workforce to face the digital era by examining three main indicators: education level, ownership of information and communication technology (ICT) devices, and frequency of internet access. A descriptive quantitative approach was employed, utilizing secondary data from the 2024 official statistics published by BPS. Findings reveal that most of Tolitoli’s working-age population holds only basic to intermediate education, with limited access to ICT and the internet. The region's Digital Readiness Index (DRI) is estimated at 40–45%, classified as low. These findings highlight the urgent need for strategic interventions, including digital training, strengthening vocational education, and promoting a more inclusive and contextual digital literacy culture.